An investigation of clothing for elderly: emphasizing safety, protection and functional attributes / Shahrizad Fitri Mustapha ... [et al.] - Mustapha, Shahrizad Fitri; Nahrawi, Shuhaila; Dahaman, Rizal Azni; Zainun, Norzaleha (2021)
This research discussed the potential of combinations between high-tech fashion and multi-function elements as a new approach in producing outdoor clothing for senior citizens. The design is appropriate with weather condition in Malaysia with high-tech fabric function that aims to provide comfort for users. The clothing is designed to provide protection and insulation. The objectives of this research are to: (i) identify the new potential of hi-tech wearable that is suitable to wear in Malaysia, (ii) examine the design styles of outdoor clothing that portray the comfort and protection for old age, and (iii) identify the design elements that can meet the multi-function purposes. Senior citizens become the primary focus in this study because elderly clothing is a line of clothing that is both age appropriate, easy to wear and easy to care for. As we know, it becomes more difficult for them to move, stretch, bend and twist. This clothing focuses on the challenges faced by those with decreased levels of mobility, arthritis, scoliosis, podiatry concerns, and incontinence issues.